2021
DOI: 10.1016/j.celrep.2021.109688
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Bos taurus RECQL is predominantly monomeric and more active than oligomers

Abstract: There is broad consensus that RecQ family helicase is a high-order oligomer that dissociates into a dimer upon ATP binding. This conclusion is based mainly on studies of highly purified recombinant proteins, and the oligomeric states of RecQ helicases in living cells remain unknown. We show here that, in contrast to current models, monomeric RECQL helicase is more abundant than oligomer/dimer forms in living cells. Further characterization of endogenous BtRECQL and isolated monomeric BtRECQL using various appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…However, most recently, Xi’s lab reported that the unwinding activity of Bos taurus RECQ1 was modulated by its oligomeric states. In addition, both monomeric BtRECQ1 and monomeric human RECQ1 unfolded intramolecular G4 DNA as efficiently as human BLM helicase ( Liu N.-N. et al, 2021 ). There are evidences suggest that RECQ1 can function through interaction with G4s.…”
Section: G-quadruplex Unwinding Helicases and Their Functionsmentioning
confidence: 99%
“…However, most recently, Xi’s lab reported that the unwinding activity of Bos taurus RECQ1 was modulated by its oligomeric states. In addition, both monomeric BtRECQ1 and monomeric human RECQ1 unfolded intramolecular G4 DNA as efficiently as human BLM helicase ( Liu N.-N. et al, 2021 ). There are evidences suggest that RECQ1 can function through interaction with G4s.…”
Section: G-quadruplex Unwinding Helicases and Their Functionsmentioning
confidence: 99%
“…The ability of RECQL1 to restart forks through branch migration of a reversed fork was shown to require its ATPase activity ( 14 ). While the p.A459S mutation lies outside the RECQL1 helicase domain, it has been previously demonstrated that mutating conserved cysteine residues within the ZBD compromises both its ATPase and DNA unwinding activities ( 11 , 12 ). In keeping with this, we have shown that the p.A459S mutation also substantially reduced the ATPase, DNA unwinding, and branch-migrating activities of RECQL1.…”
Section: Discussionmentioning
confidence: 99%
“…It can also catalyze branch migration of Holliday junctions and D-loops, unwind G4 structures, and promote single-strand DNA annealing (SSA). However, unlike other human RecQ helicases, it acts poorly to unwind RNA:DNA hybrids or displace Rad51 bound to ssDNA ( 11 , 12 ). Despite its demonstrated biochemical activities, mice devoid of this enzyme are phenotypically normal ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…The malachite green assay (MAK113; Sigma‐Aldrich) was used to test the ATP hydrolysis activity of ToPif1 and its mutants by measuring the release of inorganic phosphate as previously described (Liu et al , 2021). Briefly, 100 nM purified protein and ATP (concentrations ranging from 0 μM to 400 μM) were incubated with or without a 1 mM DNA effector (S 18 H 11 , sequence were shown in Table EV1) using a VICTOR Nivo Multimode Microplate Reader (PerkinElmer, Waltham, MA, USA).…”
Section: Methodsmentioning
confidence: 99%